A new polyoxygenated farnesylcyclohexenone from Fungus Penicillium sp. Issue 1 (2nd January 2016) - Yang, Yabin; Yang, Fangfang; Zhao, Lixing; Duang, Rongting; Chen, Guangyi; Li, Xiaozhan; Li, Qiling; Qin, Shaohuan; Ding, Zhongtao
Abstract : A new polyoxygenated farnesylcyclohexenone, peniginsengin A (1 ), was isolated from the fermentation of Penicillium sp. YIM PH30003, an endophytic fungus associated with Panax notoginseng (Burk.) F. H. Chen. The structure was assigned based on a combination of 1 D and 2 D NMR and mass spectral data. The cytotoxicity and antimicrobial activities of compound1 were investigated. Abstract :